N-Diamondynes: Expanding the family of carbon allotropes. (September 2018) - Costa, Deyse G.; Henrique, Fábio J.F.S.; Oliveira, Felipe L.; Capaz, Rodrigo B.; Esteves, Pierre M.
Abstract: A new family of carbon allotropes, called n- diamondynes, is proposed based on the insertion of acetylide units between the sp 3 -hybridized carbon atoms of diamond. We perform density-functional theory calculations in order to predict their structural, mechanical, vibrational and electronic properties. The variation of these properties with respect to the number of the acetylide moieties is systematically investigated. In addition, using grand-canonical Monte-Carlo simulations with classical force fields, we explore the potential of these porous materials for gas adsorption. Graphical abstract: Image 1